Upgrading of The Single Point Laser Vibrometer into a Laser Scanning Vibrometer - Kavalir, Tomas; Krizek, Michal; Sika, Jiri; Kindl, Vladimir (Communications - Scientific letters of the University of Zilina, 2018)
The paper proposes a construction design of measuring device for fast and reliable non-contact modal analysis of object surfaces which cannot be measured using classical methods. The design combines conventional non-contact laser interferometer with an active optics module to be able to measure multiple points in a rapid sequence. The paper briefly discusses all the key constructional components and describes in detail the system functional layout. It also introduces the experimental measurement of a HV transformer under operation to demonstrate the system functionality.